Ultrasonic and Electrocoagulation Technologies in Wastewater Treatment and Material Circulation - Khai, Nguyen Manh; Thi Mai, Nguyen; Minh Hang, Tran Thi; Van Thanh, Dang; Tien Duc, Pham; Trang, Hoang Minh (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 2, 2024)
Due to the emergence of new and persistent pollutants in wastewater, various advanced oxidation processes (AOPs) such as ultrasonic technology and electrocoagulation have been developed and employed for pollutant degradation, removal, and recovery from wastewater. In this study, we investigated the principles, influencing factors, and practical applications of several methods combining ultrasound and electrocoagulation with catalysts and demonstrated the efficiency of each method. Additionally, we analyzed the challenges associated with these ultrasonic methods and electrocoagulation in removing antibiotics and recovering pollutants from aqueous solutions and suggested solutions to these problems. Materials recovered after treatment can be utilized to improve soil quality.